Pendampingan Pembelajaran Menggunakan Metode ICT Untuk Meningkatkan Minat Belajar Di Madrasah Diniyah Roudlotul Huda Desa Sukorejo Kecamatan Sukorejo - Mukaromah, Binti Awalul; Witasari, Rinesti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article explains the pattern of delivery of Islamic jurisprudence material for Islamic prayer material using ICT methods implemented in Sukorejo Village, Sukorejo District, Ponorogo Regency. Assistance in learning fiqh material about prayer is considered very important and must be taught from an early age, because prayer is the main thing which will be the first to be reckoned with in the afterlife and prayer is also the main foundation for Muslims in the world. This mentoring activity aims to teach and understand children, especially at Madrasah Diniyah Roudlotul Huda, Sukorejo Village, about how to carry out prayer practices properly and correctly. The objects or targets of this activity are children at Madrasah Diniyah Roudlotul Huda, Sukorejo Village. The method used in this mentoring activity is ABCD (Asset Based Community Development). In practice, this activity was carried out for three days. This mentoring activity is carried out because many children do not understand, most of them only understand in theory, while the practice is still lacking. The result of this assistance is that the children understand more about how to pray properly and correctly, both in terms of movement and reading, and it can be seen that after this prayer practice the children are much better than before. This mentoring activity also received more attention from the institution, santri guardians, and the environment and also extraordinary enthusiasm from the children of Madrasah Diniyah Roudlotul Huda, Sukorejo Village, Sukorejo District, Ponorogo Regency so that the activity could run well, at least it could make a difference to the children. -child.